Interferômetro de Michelson na abordagem do clube do problema. - MACIEL, Luis Eduardo de Carvalho (2024)
In this work, inspired by the teaching-learning methodology of the Problem Club (CP), we investigate the Michelson interferometer (IM), both theoretically and experimentally, and we use MI to measure the wavelength of a laser source, and the refractive index of microscope slides. The Problem Club is an initiative that is based on the idea of learning by project or learning through problem solving and is composed of three general stages: (1) The student is taught from an early on to use scientific method tools (data collection, construction from the scientific foundations of the problem, raising hypotheses, testing theories and hypotheses, et. cetera) for solving book problems; (2) The student is encouraged to present their resolutions to be fully debated in the group. It is important to note that the problem chosen by the student is announced to the other participants so that they can have time to make their analysis and bring contributions to the debate; (3) A problem is chosen to be implemented in the laboratory. In the case study discussed, the wavelength of light was determined by counting the interference fringes (intensity maxima), and the refractive index was determined by rotating the refracting object in one of the interferometer's branches. The experimental values obtained are in good agreement with measurements performed via other experimental methods and data from the literature, with percentage errors of 0.85% for the wavelength, 0.9% and 0.2% for the two measurements of the index of refraction. We conclude that the applied problem club method was effective as a physics teaching and learning tool, providing the student with greater autonomy to solve theoretical and experimental problems. We proved the potential of the IM as a tool for the study of wave phenomena and an apparatus for scientific research. Finally, we believe that the experimental work carried out here can perfectly be inserted into the practices of the special laboratory discipline of the Physics courses at the Federal University of Pará.